General chemistry - Ebbing, Darrell D.; Gammon, Steven D. (New York Houghton Mifflin College Div, 2009)
This is a used book. If applicable online access or codes are not guaranteed to work. Shelf and edge wear to boards. There are writing marks in the book. However, most of the pages are clean.
Import.
Keywords: general chemistry